オーロラ粒子の研究: そのグローバルな特徴と磁気圏-電離圏結合過程 - Shiokawa, Kazuo; 12529; 塩川, 和夫; 12530 (1994)
名古屋大学 Nagoya University 博士(理学) Magnetosphere-ionosphere coupling processes associated with auroras have been studied on both the local and the global scale and on various magnetic activities and substorm phases. The magnetospheric electron density nM and thermal energy EM above auroral arcs have been estimated by fitting the accelerated Maxwellian distribution function to the electron energy spectra observed by two Antarctic rockets and the Defense Meteorological Satellite Program (DMSP) satellites. The fitting based on the adiabatic theory of auroral particle motions between the magnetosphere and the ionosphere. The theory also shows that the field-aligned current j∥is linearly proportional to the fieldaligned potential difference V∥. The proportional constant corresponds to the adiabatic conductivity K along a magnetic field line. The main finding of this study is that the estimated magnetospheric electron density nM and the adiabatic conductivity K decrease with increasing V∥(obtained from the statistical study using the DMSP particle data). This fact suggests that field-aligned potential differences are formed to maintain field-aligned currents in the magnetosphere-ionosphere coupling process. Several features of electron heating during field-aligned acceleration have been studied in detail using the rocket data and on a global scale using the DMSP data. The different structures of magnetospheric electron densities above quiet and active auroral arcs are found from the rocket observations. The DMSP observations suggest that the estimated electron density and thermal energy in the magnetosphere are very useful parameters for identifying the magnetospheric source region of precipitating particles. Another interesting result of the present study is that we have shown the global changes in the precipitating particle features associated with substorm phases. The Central Plasma Sheet (CPS) type electron precipitation region expands toward a higher latitude around midnight and toward a lower latitude around ...